Ss9Screening and Identification of melanin producing Actinomycetes - Samer M. Al-Hulu (Al-Qadisiyah Journal of Pure Science, 2017)
Twenty-five soil samples were collected from Hilla city. Ten isolates of Actinomycetes were identified. These isolates were screened for melanin production. Out of these two isolates (Actinomycetes .2, Actinomycetes .5) were produce brown pigment on peptone- yeast extract agar. These isolates were cultured on tyrosine broth and found Actinomycetes .2 were able to produce melanin by formation red color. Actinomycetes .2 was grey aerial mycelium, yellow – brown substrate mycelium and able to ferment glucose, sucrose, fructose and xylose. Actinomycetes .2 isolate showed antibacterial activity against S.aureus, E.coli with inhibition zone (15,20)mm subsequently. Melanin was extract and showed antibacterial activity against S.aureus (18mm) and E.coli (19mm) and antifungal activity against C.albicns with 15mm inhibition zone.